Digital Transformation in MSDM as the Key to Companies' Adaptation to Changing Global Business Ecosystems - Endang Sarwiningsih Setyawulan; Windi Novia Ratri Wardhani (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2025)
This research aims to explore the role of digital transformation in Human Resource Management (HRM) as the key to corporate adaptation to changing global business ecosystems. Using a qualitative approach with a literature study type, this study analyzes various scientific articles, research reports, and case studies related to the application of technology in MSDM. The findings of the study show that digital transformation in HR contributes significantly to improved operational efficiency, better management of employee performance, and flexibility in employee training and development. In addition, digitalization in MSDM allows companies to respond quickly to external changes, such as global crises or dynamic market changes. However, challenges such as resistance to change, limited digital skills, and data security issues remain major obstacles in the implementation of digital transformation. Strong digital leadership and effective change management are necessary to ensure the success of this transformation. The study also found that companies that have implemented digital transformation in MSDM are better prepared to adapt to the changes that occur in the global business ecosystem, thereby maintaining the competitiveness and sustainability of their businesses. This research provides important insights for companies looking to increase the use of technology in HR to adapt to rapid changes and improve organizational performance.